Modification of Surgical Instruments: A Need of the Hour - Ghulam Rasool Tariq; Rehman, Saqib Ur; Uzma Rasool (Pakistan Armed Forces Medical Journal, 2024)
Objective: To modify some basic surgical instruments for surgeon comfort and better operative results without compromising patient safety. Study Design: Prospective longitudinal study. Place and Duration of Study: Combined Military Hospital, Tarbela Pakistan, from Aug 2022 to July 2023. Methodology: A total of 100 patients needing various surgical procedures were included in the study. Four commonly used instruments, i.e., Needle Extractor, Deaver Liver Retractor, Mayos’ Needle Holder and Spermatic Cord Holding Forceps, were picked up for modification. A blacksmith modified them in Tarbela under the direct supervision of the 1st author who conceptualised them. Then, they were practically tested by the 2nd author in Combined Military Hospital Tarbela on 100 patients for Needle Extractors, 20 for Liver Retractor, 12 patients for Angled Needle Holder and 25 for Cord Forceps. The 3rd author did the graphic design. Their functioning was graded/categorised into excellent, good, satisfactory and poor, considering surgeon comfort and patient safety. Results: Excellent functioning (100%) of almost all instruments was achieved with surgeon comfort and patient safety in mind, except for the Liver Retractor, which needs a little further modification/alteration for optimal operative results. Conclusion: Emphasis is given to the modification of surgical instruments by the young budding surgeons who have ample potential for that and need encouragement in this regard.